Excess of mesotheliomas after exposure to chrysotile in Balangero, Italy. Issue 12 (4th June 2008) - Mirabelli, D; Calisti, R; Barone-Adesi, F; Fornero, E; Merletti, F; Magnani, C
Abstract : Background: Chrysotile from the mine in Balangero, Italy is considered to be free of tremolite. In a cohort study of miners and millers only two pleural cancers were reported, a finding considered to indicate that chrysotile has a low potency for inducing mesothelioma. However, follow-up ended in 1987 and white-collar workers and the employees of subcontractors were not studied. Methods: To complete the case ascertainment, the study searched the Registry of Malignant Mesotheliomas of Piedmont for records of cases of pleural mesothelioma among the following: mine employees; employees of subcontractors or of other firms transporting or refining Balangero asbestos, asbestos ore or mine tailings; individuals exposed to air pollution from the mine or living with mine employees; and individuals exposed to mine tailings from Balangero. Results: The study identified four new cases of pleural mesothelioma among blue-collar workers in the mine, in addition to the two reported in the cohort study. Thus, six mesotheliomas occurred, compared to the 1.5 expected (p<0.01). The study also identified three mesothelioma cases among white-collar employees at the mine, five in workers in the mine hired by subcontracting firms, and three among workers processing Balangero chrysotile outside the mine. Finally, 10 additional cases due to non-occupational exposure or exposure to re-used mine tailings were identified. Conclusions: The cluster of 14 mesothelioma cases among workers who were active in the mine and 13 among other people exposed to Balangero chrysotile provides further evidence that tremolite-free chrysotile is carcinogenic.